Literature Review : Study of molecular mechanism level of NSAID class of drugs as COX-2 inhibitors - Zakiyah, Wildani; Sukma Wibowo, Sepvia Putri; Elyyana, Nina; Nur Darmawan, Shiyami Aulia; Lestari, Sepiyani Ayu; Sa'diyyah, Nur; Malau, Jekmal; Mulki, Munir Alinu (Sean Institute, 2022)
NSAIDs (Non-Steroid Anti-Inflammatory Drugs) are drugs that can treat pain and inflammation. The therapeutic effect of NSAIDs as anti-inflammatory analgesics is that they have the ability to inhibit the biosynthesis of prostaglandins which are pain mediators. This prostaglandin has a major role in inhibiting the COX enzyme (cyclooxygenase) in which COX has two isoforms, namely COX1 isoenzyme (non-selective) and COX2 isoenzyme (selective). Tricyclic COX-2 selective inhibitors work by blocking COX-2. COX-2 binds to PD-L1 via the PGE2 pathway and affects macrophages in suppressing myeloid. COX-2 has functions including producing reactive oxygen species that are responsible for DNA damage, activating substances that deviate from intracellular pathways such as the MAPK and PI3 K/AKT pathways, activating STAT3, inducing Bcl-2, and producing growth factors including growth factors. epidermal (EGF)) and fibroblast growth factor (FGF).